Prevalence of sexually transmitted infections and sexual risk behaviours among men who have sex with men in Zagreb, Croatia - Božičević, Ivana (Array, 2009)
We used respondent driven sampling (RDS) to recruit MSM in Zagreb during 2006. Participants completed a questionnaire and provided blood, urine, and a self-collected rectal swab which were analyzed for the presence of the following infections: HIV (EIA, WB, PCR on pooled samples and if positive on an individual sample), syphilis (TPHA), gonorrhoea (rectal and urine samples for PCR), chlamydia (rectal and urine samples for PCR), HSV-2 (EIA, WB), hepatitis A, hepatitis B, and hepatitis C (EIA and PCR on pooled or individual sera). We recruited 360 MSM. Almost 60% of MSM had anal sex with a casual partner in the previous year, and 45.5% of them did not use condoms at least once with these partners. One third of MSM reported bisexual orientation. HIV infection was diagnosed in 4.5% of MSM. The seroprevalence for viral pathogens was: HSV-2, 9.4% ; hepatitis A, 14.2% ; hepatitis C, 3.0% ; anti-HBc, 9.2% ; anti-HBs, 17.9%, HBs Ag, 0.9%. Seroprevalence of syphilis was 10.6%. Prevalence of chlamydia and gonorrhoea was 9.0%, and 13.2% respectively. We found a low prevalence of HIV among MSM in Zagreb. However, syphilis gonococcal, and chlamydial infections were higher than expected from the official surveillance data. This argues for a need for interventions to diagnose, treat and prevent HIV and other STIs in MSM in Zagreb, Croatia.